Penatalaksanaan Pasien Wanita 63 Tahun dengan Tuberkulosis Paru dan Diabetes Melitus Tipe 2 Melalui Pendekatan Dokter Keluarga di Puskesmas Susunan Baru - Desti Dwi Rahmah; Aila Karyus (Medula, 2023)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, which can attack the lungs and other organs. As many as 10.6 million people worldwide suffer from tuberculosis (TB) with an increase in the incidence rate of 3.6% between 2020 and 2021. Type 2 diabetes mellitus (DM) is one of the most important risk factors for worsening TB with a risk of active TB 2 -4 times higher in individuals with type 2 DM than non-DM. The study conducted in the form of a case report. Data were obtained through anamnesis, physical examination, laboratory examination, and medical records at PUSKESMAS. The assessment carried out based on the initial holistic diagnosis, process, and the final of the study both quantitatively and qualitatively. Based on the study, case a 63-year-old female patient with complaints of dry cough and phlegm for 2 months accompanied by an itchy throat, chills, decreased appetite and body weight. The patient has type 2 DM since 6 years. Family doctor services carried out to identify risk factors, clinical problems, as well as evidence-based medicine with patient management through a family approach, patient-centred, and community-oriented. Interventions done both medically and non-medically in the form of patient and family education about pulmonary tuberculosis and type 2 DM. Evaluation after the intervention obtained a decrease in fasting blood sugar, an increase in knowledge about the patient's disease, and an improvement in eating patterns.